National level indicators for gender, poverty, food security, nutrition and health in Climate-Smart Agriculture (CSA) activities - Duffy, Colm; Murray, Una; Nowak, Andreea C.; Girvetz, Evan Hartunian; Corner-Dolloff, Caitlin; Twyman, Jennifer; Huyer, Sophia; Jarvis, Andy; Spillane, Charles (2017)
At the global, regional and national levels, governments, donors, research institutions, non-government organizations and private companies are more strategically linking climate change and agriculture development activities, through initiatives such as the Global Alliance for Climate-Smart Agriculture (CSA). In this context, it is necessary to have robust metrics and indicators for measuring progress towards CSA-related goals. This requires strategic selection of indicators to assess the type of impact (negative/positive) of adaptation and mitigation activities on specific societal groups (e.g. ethnic groups, women, youth, etc.) to ensure livelihoods are positively impacted by CSA interventions. Gender, poverty, food security, nutrition and health indicators have not been extensively used in CSA programming and planning to date. In this paper, we review a range of gender, poverty, food security, nutrition and health indicators relevant for national planning processes for CSA promotion and scale out. We focus on the CSA CPs developed by the International Center for Tropical Agriculture (CIAT) in collaboration with the CGIAR research program on Climate Change, Agriculture, and Food Security (CCAFS). The CSA CPs are being developed as an instrument to open dialogues on the baseline situation, identifying opportunities, and challenges for CSA in various countries. The CPs are generated by the CGIAR CCAFS program with national partners, especially those involved in CSA related planning processes, to feed into analytical multi-stakeholder processes to prioritize CSA investment portfolios for scale-up and scale out. Using a ranking system based on data relevance, availability, and applicability to multiple national contexts, we identified a set of indicators that respond to the need for better integration of gender, poverty, food security, nutrition and health concerns when approaching CSA. Strengthened integration of poverty reduction, food security and gender equality indicators into CSA assessments, including the CPs, has been identified by CCAFS as a priority to strengthen the focus on resilience/adaptation efforts, specifically highlighting evidences of gender differences. It can also serve to highlight potential gaps in availability of and access to resources and capacities to adopt CSA practices and technologies among different societal groups (women, men, youth, ethnic groups). Rather than re-invent new indicators, it is important that, where possible, existing national-level indicators can be repurposed for tracking CSA impacts over time on poverty reduction, food security and gender equality outcomes.